Implementasi Kurikulum Merdeka Pada SD-IT di Kecamatan Koto Baru Kabupaten Dharmasraya - Maulani, Raisha Fadiyah; Hidayati, Abna; Syafril, Syafril; Rahmayanti, Elsa (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to analyze the implementation of the Independent Curriculum in Integrated Islamic Elementary Schools (SD-IT) in Koto Baru District, Dharmasraya Regency. The Independent Curriculum was introduced by the government in 2021 as an effort to restore learning affected by the COVID-19 pandemic and improve the quality of education through a project-based learning approach. This study evaluates teacher readiness, the implementation process, and the impact on student motivation in the implementation of this curriculum. This study uses a quantitative approach with a descriptive method. The research population is based on a sample taken from data obtained in the form of numbers. In this study, the samples taken were 64 teachers and 33 Class V students at SD IT Al-Ihsan, SD-IT Al Bina, and SD-IT Sakinah. Data collection was carried out using a closed questionnaire that had previously been validated to experts (judgment experts). The data obtained in the field was analyzed descriptively. The results of the research on teachers and students of SD-IT in Koto Baru Dharmasraya District show that the implementation of the Independent Curriculum for teachers and students has been very good with an average score of 85.68% for teachers and 87.27% for students